PENGARUH MODEL TGT BERBANTUAN LEAFLET PADA MATERI MONERA TERHADAP HASIL BELAJAR SISWA KELAS X - Desti, Desti; Ningsih, Kurnia; Syamswisna, Syamswisna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to know the influence of lesson model Teams Games Turnament (TGT) by using Leaflet on the lesson Monera for grade X in SMAN 1 Sungai Pinyuh. The research method was Quasi Experimental Design with research design Nonequivalent Control Group Design. Technique of data collecting used was intact group whether grade X MIA 3 as the experiment class and grade X MIA 2 as control class. The instrument was 25 numbers of multiple choice test. Based on the data analysis, it has been gained the average of students’ study result which have been taught by using Teams Games Turnament (TGT) using Leaflet was 20,39, meanwhile the students’ which have been taught by using conventional learning was 17,78. From the U Mann Whitney test, it has been gain Zhitung < Ztabel was -2,75 < -1,96 which meant there was significant differences between students’ study result which have been taught by using Teams Games Turnament (TGT) using Leaflet and students’ which have been taught by using conventional learning. The effect size number that has been gained was 0,69 and has been categorized as moderate and given influences 25,49%.Keywords: influence, model Team Games Turnament (TGT) using Leaflet, Monera lesson